Biofloc Formation Strategy Effects on Halophyte Integration in IMTA with Marine Shrimp and Tilapia - Mayra da Silva Gonçalves; Andrezza Carvalho; Jorge Santos; Mariana Holanda; Luís Henrique Poersch; César Serra Bonifácio Costa (Aquaculture Journal)
The incorporation of aquaponics into saline integrated multitrophic aquaculture (IMTA) systems, employing biofloc technology (BFT), relies on the cultivation of halophytes capable of withstanding the physical–chemical conditions created by the unique microbial communities in BFT systems. This study aimed to evaluate the integration of the halophyte Salicornia neei with tilapia (Oreochromis niloticus) and marine shrimp (Litopenaeus vannamei) reared in BFT systems dominated by chemoautotrophic (CHE) and heterotrophic (HET) microorganisms over a period of 84 days in southern Brazil. Each BFT treatment had three replicates, composed of IMTA units. The stocking densities were 400 ind. m−3 (17 m3 circular tanks), 44 ind. m−3 (4 m3 circular tanks), and 30 ind. m−2 (4.8 m2 hydroponic benches) for shrimp, fish, and halophyte, respectively. The highest S. neei individual shoot production (up to 31 g per 30 days) was observed in the CHE treatment, along with favorable agronomic characteristics, possibly due to overall elevated nitrate (98.41 mg N−NO3 L−1) and phosphate concentrations (4.62 P−PO4 L−1). Shrimp in the CHE treatment displayed higher average final weight, specific growth rate, productivity, and survival (11.24 g, 2.88% day−1, 3.86 kg m−3, and 90%, respectively) compared to the HET treatment. Results indicated no significant difference in tilapia zootechnical performance between treatments.